Experimental Study on the Sensitive Emission Lines Intensities of Metal Samples Using Laser Ablation Technique and Its Comparison to Arc Discharge Technique - Eko Susilowati; Tjung Jie Lie; Hendrik Kurniawan (Institute for Research and Community Services, Institut Teknologi Bandung, 2004)
An experimental study has been carried out to measure the sensitive emission lines intensities of several metal samples (copper, zinc, silver, gold, gallium, nickel, silicone and iron) using laser ablation technique conducted in low pressure surrounding gas by means of Laser Induced Shock Wave Plasma Spectroscopy (LISPS) and in atmospheric pressure region using Laser Induced Breakdown Spectroscopy (LIBS). In both cases the Nd-YAG laser was operated at its fundamental wavelength of 1.064 nm with pulse duration of 8 ns and its intensity tightly focused on the metal samples in helium or air as an ambient gas. The laser energy was fixed at approximately 100 mJ using a set of neutral density filters placed tilted in front of the laser output window. The result of the intensity measurements showed a good agreement which those obtained using arc discharge technique as shown in Massachusetts Institute of Technology Wavelength Table. Further evaluation of these results on the basis of standard deviation leads to the conclusion that LISPS is more favorable for quantitative analysis compared to LIBS. It was further shown that replacing air by helium gas at low pressure improve to some extent the LISPS reproducibility and sensitivity.